Objective Cognitive Outcomes and Subjective Emotional Sequelae in Litigating Adults with a Traumatic Brain Injury: The Impact of Performance and Symptom Validity Measures. (16th June 2022) - Uiterwijk, Daniel; Stargatt, Robyn; Crowe, Simon F
Abstract: Objective: This study examined the relative contribution of performance and symptom validity in litigating adults with traumatic brain injury (TBI), as a function of TBI severity, and examined the relationship between self-reported emotional symptoms and cognitive tests scores while controlling for validity test performance. Method: Participants underwent neuropsychological assessment between January 2012 and June 2021 in the context of compensation-seeking claims related to a TBI. All participants completed a cognitive test battery, the Personality Assessment Inventory (including symptom validity tests; SVTs), and multiple performance validity tests (PVTs). Data analyses included independent t -tests, one-way ANOVAs, correlation analyses, and hierarchical multiple regression. Results: A total of 370 participants were included. Atypical PVT and SVT performance were associated with poorer cognitive test performance and higher emotional symptom report, irrespective of TBI severity. PVTs and SVTs had an additive effect on cognitive test performance for uncomplicated mTBI, but less so for more severe TBI. The relationship between emotional symptoms and cognitive test performance diminished substantially when validity test performance was controlled, and validity test performance had a substantially larger impact than emotional symptoms on cognitive test performance. Conclusion: Validity test performance has a significant impact on the neuropsychological profiles of people with TBI, irrespective of TBI severity, and plays a significant role in the relationship between emotional symptoms and cognitive test performance. Adequate validity testing should be incorporated into every neuropsychological assessment, and associations between emotional symptoms and cognitive outcomes that do not consider validity testing should be interpreted with extreme caution.